A multisite analysis of missed doses of antibiotics administered in hospital care. Issue 4 (14th June 2013) - Carruthers, T; Curtis, C; Marriott, J; Ray, D; Slee, A
Abstract : Objectives: The study aimed to quantify the incidence of missed antibiotic doses in acute hospitals and identify the underlying reasons using data from electronic prescribing and medicines administration systems (EPMAS), thus establishing the feasibility of determining a minimal acceptable range for missed antibiotic doses. Methods: Prescribing and administration data for antimicrobials were extracted from three hospital EPMAS (1 April 2010–31 March 2011). Data transfer protocols were developed and context mapping undertaken to ensure consistent analysis and interpretation. Total and missed numbers of antibiotic doses were calculated. The top 20 prescribed antibiotics were determined and the reasons for missed antibiotic doses were recorded. Results: A data set of 1 157 576 antibiotic administration events was compiled. The percentage of missed antibiotic doses ranged from 5.90% to 10.26% of the total. The percentage use of the 'Medicine unavailable' reason for missed antibiotic doses was a very small proportion of the total numbers of antibiotic doses prescribed (range 0.64–0.98%). Conclusions: This study has demonstrated that large data sets from different EPMAS can be used to quantify the incidence of missed antibiotic doses in acute hospitals. It is proposed that the numbers of 'Nil By Mouth' and 'appropriate clinical reasons' for dose omission provide an estimate of the maximum proportion of valid missed antibiotic doses within any hospital (range 0.3–4.6% of total antibiotic doses prescribed), so it is suggested that the acceptable level of missed antibiotics should be approximately 5% of the total number of doses intended. Active intervention by senior hospital management appears to lead to the reduction in numbers of missed antibiotic doses. Medicines supply failure was not a significant reason for missed antibiotic administration.